Camera-Recorded Extrajudicial Executions by the Islamic State (2015-2020): analysis – Statistics – Data Set - Tinnes, Judith (Perspectives on terrorism, 2022)
This Research Note provides findings from a systematic monitoring effort of visually documented extrajudicial executions perpetrated by the Islamic State terrorist group. Based on a data set covering 2,414 individuals killed between January 2015 and December 2020 (1,224 incidents) - which was compiled for ‘Perspectives on Terrorism’ in the monitoring project ‘Counting Lives Lost’ (CLL) - it presents results from long-term measures of roughly 20 incident- and victim level variables, including citizenship, gender, geographic location, execution method, and IS’ justifying arguments for the killings. Accompanied by a supplementary statistics file featuring tabular and graphical representations of the data and the full data set, it highlights temporal trends, changing dynamics, and characteristic qualitative and quantitative patterns, providing unprecedented insights into the execution activities and victimization behavior of the terrorist organization. In contrast to earlier long-term studies, it includes local victims and is not geographically limited. The findings reveal a marked downward trend in incident and casualty numbers over time yet also make clear that IS executions have not come to a halt but continue to remain a persistent phenomenon. The data suggests that the group’s territorial breakdown impacted its publicized execution activities. Patterns for conflict-related hostage killings and governance-linked Sharia executions differed significantly. More than 95% of the victims were local citizens from conflict nations (most of them Muslims), while foreigner killings were rare. Less than 1% of the victims were females. The IS’ heartlands of Iraq and Syria constituted the main execution theater. Over time, execution activities relocated on a micro-level from urban to more rural areas (especially, within Syria and Iraq) and, on a macro-level, increasingly shifted to different regions (particularly West Africa). The IS named purported ‘charges’ of the captives as the reason for its violence. The bulk of these charges were related to the conflict between the group and its enemies, while accusations that were closely tied to its implementation of territorial governance had a much lower share. While the IS is often associated with transgressive execution methods, the majority of victims were killed by shooting, yet the group accounted for an unprecedented number of beheadings. Particular types of charges and execution techniques appeared to be associated with each other. Public executions before a physical audience varied for different killing styles and charges, and significantly decreased over time. In 52 execution incidents, the IS instrumentalized minors as executioners. While over 90% of the foreign hostages garnered coverage in Western news media, less than 10% of the locals were reported.